Dhikr Therapy In Overcoming Stress; Scientific Analysis Study Of Masaru Emoto The True Power Of Water - Rahayu, Anggit; Azwar, Alfi Julizun; Kholifah, Umi Nur (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2024)
This research aims to discuss Masaru Emoto’s concept regarding the influence of words on water as presented in his work “The True Power Of Water” and provide a scientific review of dhikr therapy in addressing stress in accordance with Masaru Emoto’s concept. The study employs a qualitative descriptive method through a literature review. Both primary and secondary data serve as sources for this investigation. The research findings reveal that water exposed to positive words, such as dhikr, from beautiful hexagonal-shaped crystals, while to the opposite occurs with negative words. From a scientific perspective, utilizing dhikr therapy with water as medium can assist in alleviating stress. This is attributed to water’s ability to absorb dhikr messages as a form of therapy; chanting dhikr can soothe the soul and generate positive energy, thereby altering the water’s quality. In conclusion, the use of positive words spoken to the body through water as a medium has the potential to alleviate stress disorders when practiced with patience and confidence in the belief that Allah can heal all deseases through the recited water.